Assessment of Baseflow Characteristics and Environmental Flow Allocation in the Welo Sub-Watershed, Central Java - Wahlul Sodikin; Pitojo Tri Juwono; Mohammad Sholichin (Jurnal Penelitian Pendidikan IPA, 2025)
This study assesses baseflow characteristics and environmental flow (EF) requirements in the Welo Sub-Watershed, Central Java, Indonesia—a region increasingly affected by land use change and climate variability. Using 30 years of daily streamflow data (1994–2023), baseflow was separated using the Fixed Interval Method with analysis conducted in Excel and the Hydrologic Engineering Center’s Hydrograph Analysis (HEC-HMS). EF was estimated using both the Tennant Method and Flow Duration Curve (FDC) analysis. Results indicate that average dry-season baseflow is 0.79 m³/s, while the reliable flow (Q80) averages 1.02 m³/s. EF estimates are 0.43 m³/s (Tennant) and 0.54 m³/s (FDC). Under normal hydrological conditions, baseflow exceeds EF thresholds. However, peak irrigation demand reaching 1.30 m³/s surpasses both baseflow and Q80 during dry periods. This suggests periods of ecological stress and potential conflict among water users. These findings underscore the need for integrating EF targets into local water resource planning to safeguard ecosystem function and ensure sustainable water allocation.